(untitled) (European Journal of Engineering Science and Technology, 2019)
Surface properties are important for materials that are in contact with each other. Especially when the lubrication conditions are inadequate, the properties of the materials are the main feature that determines the wear behavior. Bimetal journal bearing materials are machine materials that are subjected to load and motion. For this reason, attempts are made to improve the wear behaviors of these materials and they are frequently investigated in the literature. In the present study, in order to improve the tribological characteristic of the steel-backed copper-based bimetallic material, SAE 49 was coated with tin, lead and Al2O3 powders using cold spray process and the microstructure, hardness and wear properties of the samples were investigated. It was observed that the Al2O3 particles were homogeneously dispersed by the cold spray process. The increasing amount of soft phases such as tin and lead caused decreasing in hardness. However, these soft phases that had solid lubricant properties in the structure and the hard phase such as Al2O3 improved the wear behavior of the sample.